La participación de México en misiones de paz de las Naciones Unidas - Reyes, Guillermo (Revista Mexicana de Política Exterior, 2022)
Guillermo Reyes believes Mexico’s participation in United Nations peace missions to be an unresolved foreign policy and national security issue, whose implications and scope require in-depth analysis and debate. After giving us an overview of Mexico’s foreign policy vis-à-vis these missions since they were set up over 60 years ago, the author goes on to discuss our financial contribution to them, the extent to which we have participated in decisions to create or disband them and the participation of our civilians and soldiers in them. The un’s primary objectives, such as peace-keeping efforts and international security, remain valid and are in line with national interests, he says, adding that, in light of the current situation and the challenges we face, no country can afford to sit on the sidelines or wax indifferent to threats to world peace. Over and beyond their military aspect, the author believes that the benefits of participating in these missions greatly outweigh the cost and that they should be used as a tool to further our foreign policy and national security strategies, within a framework of international cooperation that is in keeping with our constitutional principles.